Analisis Pengaruh Kompensasi Keuangan dan Lingkungan Kerja pada Produktivitas Karyawan - Wisnu Hardiyanto; Abdul Manap Wardoyo (Jurnal Manajemen dan Kewirausahaan, 2016)
This study aims to examine and analyze the influence of financial compensation and working environment to employee productivity on PT. PLN (Persero) Distribution of  East Java Malang Area. The population in this study are  all employees of PT. PLN Persero Malang as 65 employees. The number of sample are 56 employees. The technique sampling uses proportionate random sampling.  Data analysis uses a multiple regression analysis. The results of this study shows that the financial compensation and working environment have positive and significant impact to employee productivity. Working environment variable has a dominant influence to employee productivity.https://doi.org/10.26905/jmdk.v4i2.661